1990
DOI: 10.1007/bf02555036
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of bone mass and the risk of fractures in osteoporosis

Abstract: The usefulness of various bone mineral measurement techniques is a subject of current controversy. In order to explore whether disparate conclusions may have arisen from differences in analytic methodology, data from published reports of bone mass and nonviolent fractures have been reanalyzed in terms of fracture risk. In the large majority of studies, reduced bone mass was associated with an increased risk of fractures. However, the magnitude of the relationship varied much more among cross-sectional studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
5

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(90 citation statements)
references
References 47 publications
4
81
0
5
Order By: Relevance
“…Large negative scores are indicative of a low BMD, and this has been shown to be associated with an increased risk of fracture. Results from studies suggest that for a 2 standard deviation dierence in bone mass there is a 2 ± 4-fold increase in fracture risk at non-spine sites 7 and a 4 ± 6-fold increase at vertebral sites. 8 Though it is recognised that these are predominantly from postmenopausal women, we have used the above to describe benchmarks of fracture risk since very few studies have been conducted either on men or on paraplegics.…”
Section: Methodsmentioning
confidence: 99%
“…Large negative scores are indicative of a low BMD, and this has been shown to be associated with an increased risk of fracture. Results from studies suggest that for a 2 standard deviation dierence in bone mass there is a 2 ± 4-fold increase in fracture risk at non-spine sites 7 and a 4 ± 6-fold increase at vertebral sites. 8 Though it is recognised that these are predominantly from postmenopausal women, we have used the above to describe benchmarks of fracture risk since very few studies have been conducted either on men or on paraplegics.…”
Section: Methodsmentioning
confidence: 99%
“…After surgery, contrast-enhanced MR is used to distinguish scar tissue from recurrent herniation (17,18). There has also been some recent interest in the high intensity zone in the posterior annulus seen in T2-weighted images (19,20).…”
Section: Visualization Of Intervertebral Disc Degeneration In Mr Imagmentioning
confidence: 99%
“…Rapid trabecular disconnectivity has been shown to affect the response to compressive stress [18]. Bone mineral density (BMD) has been shown to be one of the most important contributing factors to bone strength and a good predictor of fracture risks in osteoporosis [4,9,19,25,28]. However, many recent studies have shown that BMD alone may not be sufficient to determine the strength of cancellous bone and that the trabecular architecture may also be an important factor in determining bone strength and individual risk of fractures [3,5,11,33,34].…”
Section: Introductionmentioning
confidence: 99%